Brief introduction to Jakob von Uexküll's notion of «Umwelt» and his merleaupontyan reading (Balthazar, 2022)
This article intends to present the main notions of the theory of the Umwelt and the architecture of the new biology that the estonian-german biologist Jakob von Uexküll built in the first half of the 20th century. It will be shown how these concepts open up a new consideration of non-human animals, no longer as machine-objects, but as subjects in their own terms. Likewise, the reading carried out by Merleau-Ponty on von Uexküll in La Nature: Notes Cours du Collège de France and the influence that the Estonian-German had on the french philosopher will be exposed, in order to find meeting points that build bridges between the animal world and the human world.
Keywords: Jakob von Uexküll; Merleau-Ponty; Nature; Umwelt; animal studies